Are asylum seekers more likely to work with more inclusive labor market access regulations? - Michaela Slotwinski; Alois Stutzer; Roman Uhlig (Swiss Journal of Economics and Statistics, 2019)
In the face of recent refugee migration, early integration of asylum seekers into the labor market has been proposed as an important mechanism for easing their economic and social lot in the short as well as in the long term. However, little is known about the policies that foster or hamper their participation in the labor market, in particular during the important initial period of their stay in the host country. In order to evaluate whether inclusive labor market policies increase the labor market participation of asylum seekers, we exploit the variation in asylum policies in Swiss cantons to which asylum seekers are as good as randomly allocated. During our study period from 2011 to 2014, the employment rate among asylum seekers varied between 0 and 30.2% across cantons. Our results indicate that labor market access regulations are responsible for a substantial proportion of these differences, in which an inclusive regime increases participation by 11 percentage points. The marginal effects are larger for asylum seekers who speak a language that is linguistically close to the one in their host canton.
Keywords: F22; J61; J15; 330; Asylum policy; Asylum seekers; Economic integration; Employment ban; Labor market access regulation